2014
DOI: 10.1261/rna.041681.113
|View full text |Cite
|
Sign up to set email alerts
|

tRNA anticodon shifts in eukaryotic genomes

Abstract: Embedded in the sequence of each transfer RNA are elements that promote specific interactions with its cognate aminoacyl tRNAsynthetase. Although many such "identity elements" are known, their detection is difficult since they rely on unique structural signatures and the combinatorial action of multiple elements spread throughout the tRNA molecule. Since the anticodon is often a major identity determinant itself, it is possible to switch between certain tRNA functional types by means of anticodon substitutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 76 publications
(105 reference statements)
2
27
0
Order By: Relevance
“…One advantage to species with tRNA gene redundancy (and consequently high tRNA gene copy number) is that loss of one tRNA gene may have relatively little impact on the overall tRNA population in the cell for that particular tRNA functional isoacceptor. As a high redundancy of tRNA genes indeed facilitates tRNA anticodon mutation as previously suggested ( Rogers and Griffiths-Jones 2014 ), organisms with tRNA array units would be subjected to anticodon shifts.
F ig .
…”
Section: Resultsmentioning
confidence: 64%
“…One advantage to species with tRNA gene redundancy (and consequently high tRNA gene copy number) is that loss of one tRNA gene may have relatively little impact on the overall tRNA population in the cell for that particular tRNA functional isoacceptor. As a high redundancy of tRNA genes indeed facilitates tRNA anticodon mutation as previously suggested ( Rogers and Griffiths-Jones 2014 ), organisms with tRNA array units would be subjected to anticodon shifts.
F ig .
…”
Section: Resultsmentioning
confidence: 64%
“…To confirm our hypothesis that the changes in translation efficiencies resulted from the increased cellular demand for tRNA CCG , the tRNA which translates CGG, we decided to elevate the availability of this tRNA and examine the effect on the translation phenotype. We, and others, have recently shown that a mechanism to increase tRNA availability is a mutation in the anticodon that changes the codon specificity of the tRNA (30,31). We have shown that such anticodon-switching mutations can maintain the functionality of tRNA genes and are utilized by many species as an adaptive mechanism of the cellular tRNA pool.…”
Section: Proteome-wide Changes In Translation Efficiencies Are Allevimentioning
confidence: 87%
“…trnF-AAA has not been reported to be present in plant plastomes; however, it is an isoacceptor of trnF-GAA that is commonly found in plant plastomes, including those that are nonphotosynthetic. Mutations in anticodons (anticodon shifts) occurred many times in the evolution of several genomes, with isoacceptor shifts being more frequent than alloacceptor shifts ( Rogers and Griffiths-Jones 2014 ). The change of trnF-GAA to trnF-AAA may have been favorable, because ∼90% of all Phe codons in Epipogium are encoded by UUU.…”
Section: Discussionmentioning
confidence: 99%